2019
DOI: 10.1093/ecco-jcc/jjz032
|View full text |Cite
|
Sign up to set email alerts
|

Ciclosporin Therapy After Infliximab Failure in Hospitalized Patients With Acute Severe Colitis is Effective and Safe

Abstract: Abstract Background and Aims Options for medical management of patients with acute severe colitis [ASC] failing intravenous (i.v.) steroids are limited and include rescue therapy with either infliximab or ciclosporin. In patients failing infliximab, second-line rescue therapy with ciclosporin is an alternative. The aim of this study was to investigate the efficacy and safety of ciclosporin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The current study adds confidence to using the approach of inducing remission with CNIs-which are potent and fast-acting drugs with proven efficacy in treating patients with severe ulcerative colitis 3,[5][6][7][8]17,18,20 and then transitioning to the slower acting steroid-sparing agent, vedolizumab, for maintenance therapy. 9,10 We have shown that overlapping these two drugs is effective and safe.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The current study adds confidence to using the approach of inducing remission with CNIs-which are potent and fast-acting drugs with proven efficacy in treating patients with severe ulcerative colitis 3,[5][6][7][8]17,18,20 and then transitioning to the slower acting steroid-sparing agent, vedolizumab, for maintenance therapy. 9,10 We have shown that overlapping these two drugs is effective and safe.…”
Section: Discussionmentioning
confidence: 87%
“…Inducing remission with CNIs and transitioning to vedolizumab maintenance therapy is becoming more relevant as more patients with ulcerative colitis now have a history of previous exposure and failure to anti‐TNFs and azathioprine . Likewise, since the publication of the CYSIF and CONSTRUCT trials, which demonstrated similar short‐term response rates between infliximab and ciclosporin in the setting of acute severe ulcerative colitis, infliximab has emerged as the predominant agent used in such patients, and more patients are presenting to tertiary care centres after failing infliximab . A potential reason for nonresponse to infliximab is secondary loss of serum proteins due to monoclonal antibodies loss through an inflamed gut and in such patients, the use of a nonprotein‐based therapy for induction of remission, such as a CNI, could be useful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Practically speaking, IFX is preferred as second-line therapy. Weisshof et al assessed 40 steroid and IFX-refractory ASUC patients receiving sequential therapy with CsA; 60% achieved clinical remission within 2 weeks, and 42% had colectomy-free survival at 1 year, with no increased in adverse events, which suggest CsA therapy following rescue therapy failure with IFX can be effective and safe in ASUC [56]. A recent publication in a mixed cohort of steroid and/or anti-TNF refractory UC +/− ASUC (n = 39) has shown safety and efficacy of bridging patients from third line CsA to VDZ, with 68% colectomy-free rate at 12 months follow-up [57].…”
Section: "Third Line" Medical Therapy or Sequential Therapymentioning
confidence: 99%